Robotic-assisted total knee arthroplasty demonstrates decreased postoperative pain and opioid usage compared to conventional total knee arthroplasty - Bhimani, Samrath J. (Bone Jt Open, 2020)
AIMS: Robotic-assisted total knee arthroplasty (RA-TKA) has been introduced to provide accurate bone cuts and help achieve the target knee alignment, along with symmetric gap balancing. The purpose of this study was to determine if any early clinical benefits could be realized following TKA using robotic-assisted technology. METHODS: In all, 140 consecutive patients undergoing RA-TKA and 127 consecutive patients undergoing conventional TKA with minimum six-week follow-up were reviewed. Differences in visual analogue scores (VAS) for pain at rest and with activity, postoperative opiate usage, and length of stay (LOS) between the RA-TKA and conventional TKA groups were compared. RESULTS: Patients undergoing RA-TKA had lower average VAS pain scores at rest (p = 0.001) and with activity (p = 0.03) at two weeks following the index procedure. At the six-week interval, the RA-TKA group had lower VAS pain scores with rest (p = 0.03) and with activity (p = 0.02), and required 3.2 mg less morphine equivalents per day relative to the conventional group (p < 0.001). At six weeks, a significantly greater number of patients in the RA-TKA group were free of opioid use compared to the conventional TKA group; 70.7% vs 57.0% (p = 0.02). Patients in the RA-TKA group had a shorter LOS; 1.9 days versus 2.3 days (p < 0.001), and also had a greater percentage of patient discharged on postoperative day one; 41.3% vs 20.5% (p < 0.001). CONCLUSION: Patients undergoing RA-TKA had lower pain levels at both rest and with activity, required less opioid medication, and had a shorter LOS.